2008
DOI: 10.3390/medicina44090085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrical shock waveform and paddle positions on efficacy of direct current cardioversion for atrial fibrillation

Abstract: Objective. Direct-current electrical cardioversion is the main method for the conversion of atrial fibrillation. Its success depends on many factors. In several studies, biphasic shock waveforms have been demonstrated to be superior to monophasic shocks for termination of atrial fibrillation; however, information about impact of paddle position is controversial. Initial energy level is an object of discussions. The aim of the study was to compare a truncated exponential biphasic waveform with monophasic damped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Twenty‐five studies were selected as potentially relevant and accessed for full‐text review, and the remaining 763 studies were excluded for various reasons. Twelve studies were excluded after full‐text review, while the remaining 13 studies were included in the review involving 836 patients receiving A‐P and 856 patients receiving A‐L pad placement . One of the included studies was only found in the bibliography of several included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐five studies were selected as potentially relevant and accessed for full‐text review, and the remaining 763 studies were excluded for various reasons. Twelve studies were excluded after full‐text review, while the remaining 13 studies were included in the review involving 836 patients receiving A‐P and 856 patients receiving A‐L pad placement . One of the included studies was only found in the bibliography of several included studies.…”
Section: Resultsmentioning
confidence: 99%
“…One of the included studies was only found in the bibliography of several included studies. Google Translate was used to translate one Spanish and one Lithuanian paper to English. Of the 12 excluded studies, 11 were not prospective randomized or controlled, and one did not compare A‐P versus A‐L pad placement.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that paddles/pads should be placed under the breast tissue (LOE 5) 33 and 2 studies showed that hirsute males should be shaved before the application of pads (LOE 5). 34,35 Of the 36 studies reviewed, only 4 examined biphasic waveforms (LOE 5) 18,25,29,36 that have gained widespread use.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Most studies evaluate cardioversion (eg, AF) or secondary end points (eg, TTI). Eleven studies (LOE 5) [15][16][17][18][19][20][21][22][23][24][25] found all 4 positions (anterior-apex, anteriorposterior, anterior-left infrascapular, anterior-right infrascapular) to be equally effective in defibrillation (for VF/pulseless VT) or elective AF cardioversion success. Four studies support the anteriorposterior position (LOE 5), 26 -30 1 study supports the anterior-lateral position (LOE 5), 31 and 1 study supports the anterior-apex position (LOE 5).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…[71][72][73][74][75] There are no studies directly pertaining to placement of pads/paddles for defibrillation success with the end point of ROSC. All 4 positions are equally effective in shock success.…”
Section: Electrodes Electrode Placementmentioning
confidence: 99%